PENGUKURAN KEPUASAN PENGGUNA LULUSAN PROGRAM STUDI KOMPUTERISASI AKUNTANSI BAGI INDUSTRI - Sugiarti Sugiarti; Susena Susena; Budhi Adhiani; Sri Murtini; Rani Raharjanti (Politeknik Negeri Semarang, 2022)
This study aims to measure the level of user satisfaction of graduates of the Computerized Accounting Study Program, Department of Accounting, Semarang State Polytechnic and identify the quality attributes of graduates that need to be improved to increase graduate user satisfaction. The sample was taken as many as 20 industrial users who graduated with purposive sampling technique. The data collection method applied is a questionnaire. The data that has been collected was analyzed with the help of SPSS 26 software for Windows, then processed using the Importance Performance Analysis (IPA) model. The results of the IPA analysis on the Cartesian diagram of the 8 variables namely Reliability, Responsiveness, Confidence, Attention, Tangible, Benefit, Ease and Security indicate that the performance of the graduates of the Computerized Accounting Study Program has met expectations. However, the Computerized Accounting Study Program must always be updated on the development of science and technology so that links and matches are always created